Pengaruh Equity Market Timing Terhadap Struktur Modal Perusahaan Manufaktur di Bursa Efek Indonesia - Muniya Alteza; Nuri Lesmono Hidayah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the effect of equity market timing on the capital structure of manufacturing companies that conducted initial public offerings on the Indonesia Stock Exchange. The population in this study is the manufacturing sector companies that conduct initial offerings on the Indonesia Stock Exchange in the 2010-2015 periods. Sampling was done using the purposive sampling method. Based on the criteria, 18 companies became the research sample. Capital structure in this study is proxied by leverage while equity market timing is proxied by the market-to-book ratio. The data analysis technique used is linear regression analysis with panel data estimation. Prior to the regression analysis, the model specification test and classical assumption test were carried out to ensure that the research model was feasible to use. The results of this study indicate that equity market timing has a negative and significant effect on the company's capital structure.